Transient Global Amnesia After Cerebral Angiography With Iomeprol: A Case Report - Tiu, Cristina (Medicine (Baltimore), 2016)
Transient global amnesia is now considered a very rare complication of cerebral angiography. Various etiological mechanisms have been suggested to account for this complication, but no consensus has been reached yet. This case report documents one of the few reported cases of cerebral angiography-related transient global amnesia associated with magnetic resonance imaging (MRI) evidence of unilateral hippocampal ischemia, most probably as a consequence of a transient reduction in regional hippocampal blood flow. However, the possibility of a direct neurotoxic effect of the nonionic contrast media Iomeprol on the Cornu ammonis – field 1 neurons cannot be firmly ruled out. We describe the case of a 54-year-old woman admitted to our department for left upper limb weakness with acute onset 8 days before. The brain computed tomography (CT) scan performed at admission revealed subacute ischemic lesions in the right watershed superficial territories and a right thalamic lacunar infarct. Diagnostic digital subtraction cerebral angiography was performed 4 days after admission with the nonionic contrast media Iomeprol. A few minutes after completion of the procedure, the patient developed symptoms suggestive for transient global amnesia. The brain MRI performed 22 hours after the onset of symptoms demonstrated increased signal within the lateral part of the right hippocampus on the diffusion-weighted imaging (DWI) sequences, associated with a corresponding reduction in the apparent diffusion coefficient (ADC) and increased signal on the fluid-attenuated inversion recovery (FLAIR) sequences, consistent with acute hippocampal ischemia and several T2/FLAIR hyperintensities in the right watershed superficial territories and in the right thalamus, corresponding to the lesions already identified on the CT scan performed at admission. A follow-up MRI, performed 2 months later, demonstrated the disappearance of the increased signal within the right hippocampus on the DWI, T2/FLAIR, and ADC sequences. The precise mechanism of transient global amnesia related to cerebral angiography is still unclear, and further studies aimed to determine the definite pathophysiology of this syndrome and consequently to establish specific preventive measures are needed. Although the condition itself is considered to be self-limited, the long-term prognosis and the risk of recurrence in the cases where subsequent angiographic procedures are performed are not established yet.